Near-infrared heterojunction field modulated phototransistors with distinct photodetection/photostorage switching features for artificial visuals. Issue 24 (7th June 2022) - Han, Jiayue; Du, Xiaoyang; Zhang, Zhenhan; He, Zeyu; Han, Chao; Xie, Runzhang; Wang, Fang; Tao, Silu; Hu, Weida; Shan, Chongxin; Yang, Ming; Gou, Jun; et al.
Abstract : By incorporating organic BHJ onto graphene, graphene/ZnO/PTB7-Th:IEICO-4F shows gate tunable photodetection/photostorage switching features for the implementation of both retinomorphic vision and memorial preprocessing functions. Abstract : With the rising demand for recording, computing and image capture, advanced optoelectronic detection, storage and logic devices are highly pursued. Nevertheless, a multi-functional vision chip based on infrared detection and memory switching has never been demonstrated. Here, by utilizing the electronic extraction layer ZnO and a face-on orientation of the bulk heterojunction (BHJ), we exhibit broadband visible to near-infrared photo-response and photo-storage characters on a graphene phototransistor. Functions as photodetection and photo-storage can be switched with the variation of the gate voltage. The device demonstrates high photo-responsivity up to 1.88 × 10 6 A W −1 at 895 nm, corresponding to a detectivity of 4.8 × 10 12 Jones. Importantly, the rewritable and switching infrared optoelectronic memory function can be achieved with good retention over 10 4 s. Both retinomorphic vision and memorial preprocessing in artificial visuals are simultaneously realized by the photodetection/photostorage switching property. Such nearly all-solution processes in our phototransistors may open up the path for the large-scale and easy manufacturing of infrared multifunctional bio-optoelectronic devices.